2017
DOI: 10.18203/2320-1770.ijrcog20175280
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal birth after caesarean section: why and how?

Abstract: Background: With the significant rise in the incidence of primary caesarean section(CS) for various indications, an increasing proportion of the pregnant women coming for antenatal care, report with a history of a previous CS. This necessitates definite need to bring down the caesarean section rate, either by judicious selection of cases for primary caesarean section or by attempting vaginal delivery, following previous caesarean section (VBAC).Methods: A prospective observational study was conducted to find o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 6 publications
0
9
0
2
Order By: Relevance
“…4,[6][7][8]12,14,15 As the TOLAC rates increased, the caesarean rates decreased but the number of reports of uterine rupture and other complications during TOLAC increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,[6][7][8]12,14,15 As the TOLAC rates increased, the caesarean rates decreased but the number of reports of uterine rupture and other complications during TOLAC increased.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12][13] Mc Mahon et al found that maternal morbidity is lowest in women who have successful VBAC (0.2%), higher in women who undergo ERCS (0.8%) and highest in women who have failed TOL (3.3%).…”
Section: Discussionmentioning
confidence: 99%
“…(10,13) Other studies also showed higher rates of successful VBAC. (14,16,18,20,(22)(23)(24)(25) The probable reason for this low success rate of VBAC were that most of the cases presented in the labour room in advanced labour and were taken up for emergency repeat L.S.C.S for various indications like impending rupture, fetal distress, etc. along with nonavailability of notes of previous LSCS as 37.9% cases were unbooked.…”
Section: Discussionmentioning
confidence: 99%
“…РОССИЙСКИЙ ВЕСТНИК АКУШЕРА-ГИНЕКОЛОГА 1,2016 ОБМЕН ОПЫТОМ дение беременности и родов у женщин с рубцом на матке [2][3][4][5][6][7][8][9][10][11]. Для ведения таких родов обычно нужно дождать-ся начала спонтанной регулярной родовой деятельности [1,3,7,12,13].…”
unclassified
“…Для ведения таких родов обычно нужно дождать-ся начала спонтанной регулярной родовой деятельности [1,3,7,12,13]. Однако в условиях возрастания стоимости пребывания беременной в стационаре и увеличения пери-натального риска у пациенток данной категории при пе-ренашивании беременности такая тактика не всегда ока-зывается возможной [14,15].…”
unclassified